Comparison of the Effect of Mentorship with a Senior Student or Qualified Nurse on Knowledge and Clinical Self-Efficacy of the Second-Semester Nursing Students - Mehdi Safari Ebrahim Saraie; Zahra Bagheri; Shahin Salarvand (Kerman University of Medical Sciences, 2018)
Background Due to the pivotal role of clinical education in the nursing profession, paying attention to effective approaches in improving the quality of education is of great importance. Objectives The current study aimed at determining the effect of mentorship with senior students or nurses on knowledge and clinical self-efficacy of nursing students. Methods The current trial was conducted on 72 nursing students in Lorestan University of medical sciences in academic year 2012 - 2013. The participants selected by convenience sampling method and assigned, using stratified random blocks, to one control group which supervised by a faculty member only and two intervention groups supervised by a faculty member and a senior student or nurse as mentor. Clinical self-efficacy scale and a researcher-made questionnaire were used to measure the participants' knowledge and self-efficacy before and after the educational intervention. ANOVA and paired samples test and chi square were used to analyze the data. Results The mean score of knowledge and clinical self-efficacy increased in all the three groups, but the increase was significantly higher in the third group (the group supervised by a faculty member and a qualified nurse as mentor) than the others. Conclusions Due to the positive effects of mentorship with a qualified nurse, it is suggested that mentorship programs be included in the curriculum of nursing students.